República, Guerra Civil y represión franquista en Sierro (Almería) (1936-1947) / Eusebio Rodríguez Padilla y Juan Torreblanca Martínez - Torreblanca Martínez, Juan; Rodríguez Padilla, Eusebio (Memoria histórica de Andalucía; 10)
Bibliografía: p. 355-362. Índice